NanoSQUID magnetometry of individual cobalt nanoparticles grown by focused electron beam induced deposition. (1st December 2016) - Martínez-Pérez, M J; Müller, B; Schwebius, D; Korinski, D; Kleiner, R; Sesé, J; Koelle, D
Abstract: We demonstrate the operation of low-noise nano superconducting quantum interference devices (SQUIDs) based on the high critical field and high critical temperature superconductor YBa2 Cu3 O7 (YBCO) as ultra-sensitive magnetometers for single magnetic nanoparticles (MNPs). The nanoSQUIDs exploit the Josephson behavior of YBCO grain boundaries and have been patterned by focused ion beam milling. This allows us to precisely define the lateral dimensions of the SQUIDs so as to achieve large magnetic coupling between the nanoloop and individual MNPs. By means of focused electron beam induced deposition, cobalt MNPs with a typical size of several tens of nm have been grown directly on the surface of the sensors with nanometric spatial resolution. Remarkably, the nanoSQUIDs are operative over extremely broad ranges of applied magnetic field (–1 T < μ 0 H < 1 T) and temperature (0.3 K < T < 80 K). All these features together have allowed us to perform magnetization measurements under different ambient conditions and to detect the magnetization reversal of individual Co MNPs with magnetic moments (1–30) × 10 6 μ B . Depending on the dimensions and shape of the particles we have distinguished between two different magnetic states yielding different reversal mechanisms. The magnetization reversal is thermally activated over an energy barrier, which has been quantified for the (quasi) single-domain particles. Our measurements serve to show not only the high sensitivity achievable with YBCO nanoSQUIDs, but also demonstrate that these sensors are exceptional magnetometers for the investigation of the properties of individual nanomagnets.